Does Central Bank Capital Matter for Monetary Policy? - Tovar Mora, Camilo; Adler, Gustavo; Castro, Pedro (Washington, D.C. : International Monetary Fund, 2012)
Heavy foreign exchange intervention by central banks of emerging markets have lead to sizeable expansions of their balance sheets in recent years?accumulating foreign assets and non-money domestic liabilities (the latter due to sterilization operations). With domestic liabilities being mostly of short-term maturity and denominated in local currency, movements in domestic monetary policy interest rates can have sizable effects on central bank's net worth. In this paper we examine empirically whether balance sheet considerations influence the conduct of monetary policy. Our methodology involves the estimation of interest rate rules for a sample of 41 countries and testing whether deviations from the rule can be explained by a measure of central bank financial strength. Our findings, using linear and nonlinear techniques, suggests that central bank financial strength can be a statistically significant factor explaining large negative interest rate deviations from "optimal" levels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet